Pengelolaan Tata Ruang Kantor dalam Meningkatkan Alur Kerja Pegawai - Maryam, Maryam; Syahril, Syahril; Muizzatı Rahman, Nurul; Nurasmi, Andi (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
Office space management is an important component in improving employee workflows, with a focus on creating an efficient and productive work environment. This article discusses the role of office layout management in streamlining workflows, which is a critical factor in achieving organizational goals. Through designing strategic layouts, promoting flexibility, ensuring consistent access to resources, encouraging collaboration, supporting well-being, and integrating technology, organizations can significantly improve employee workflows and productivity. This research uses a literature study method or literature review. Data was obtained from journal articles, books, and e-books published and accessed through Google Scholar with keywords related to office layout. The data was analyzed by collecting and reviewing various sources of relevant information regarding the management of office space and employee workflows. The analysis is carried out to identify patterns and best practices in office space that can improve efficiency and productivity. This article uses qualitative data analysis from literature studies to evaluate office space management and its impact on employee workflows. The analysis process includes coding and categorizing information to identify key themes. Thematic synthesis integrates findings from multiple sources, while contextual and critical evaluations ensure the relevance and quality of the information used. The results of the study show that a well-designed office layout can improve employee workflow. Principles such as the shortest distance, the working range and the use of space should be considered. Open spaces facilitate collaboration, while closed spaces provide privacy. Ergonomic and flexible design and strategic furniture placement contribute to work comfort and productivity. With proper planning, office space planning can reduce distractions, support communication, and improve employee welfare.